Airport branding - Rudolph, Jim (Henry Stewart Talks, 2009)
Why brand an airport?, Facing the common challenges of airport branding, The re-branding process at Edmonton International Airport: research, strategic development, implementation, evaluation and continuous improvement, Focusing on brand strategy, Building brand buzz internally and externally, Delivering the brand promise every day